On the dynamics of net versus gross multipliers - Jan Oosterhaven (European Regional Science Association (ERSA), 2002)
Industries often promote their interests by arguing that they have a big impact on the rest of the economy. To substantiate such claims usually some measure of size (employment or value added) is labelled the direct effect and is then multiplied with the corresponding (gross) multiplier to calculate what is labelled the total impact of the sector or project at hand. To avoid double-counting impacts and to solve the endogenous/exogenous mix-up involved the net multiplier concept was introduced (Oosterhaven and Stelder, 2002). Both the standard (gross) multiplier and the new net multiplier are essentially static concepts. When applied in a dynamic setting the question of stability rises. The stability of the gross multipliers from the standard input-output model is based on the stability of its input coefficients. The stability of net multipliers is also based on the stability of its additional exogenous demand/total output ratios, which are unstable by definition. This note will argue that this property should not be seen as a vice but as an additional virtue of the net multiplier concept. In a closed economy, assuming fixed input price ratios, the stability of the input coefficients is a technological feature. In an open regional or national economy, with growing exogenous demand, gross multiplier stability also implies the absence of import substitution. This is unlikely whenever the growth of exogenous demand is substantial. The net multiplier concept forces the user to consider not only import substitution but also export substitution explicitly. Depending on the relative size of import versus export substitution, the net multiplier may either rise or fall, whereas the gross multiplier only rises when the economy grows. From this, the paper argues that using net multipliers is more appropriate than using gross multipliers not only in a static setting but also in a dynamic setting, that is when judging the relative importance of industries is the issue.
Keywords: 330